Cobalt oxide confined in mesoporous SiO2 as effective catalyst for CO oxidation - Liu, Tao; Ju, Xiaoqiu; Hu, Zhixin; Xie, Rongrong (Microporous and mesoporous materials, 2022)
Ordered mesoporous SiO2 samples (SBA-15) with different pore sizes were prepared as carriers, and a series of catalysts (CoOx@SBA-15(X)) were synthesized to confine CoOx in SBA-15 through the solid-state grinding method for CO oxidation. The characterization results showed that the aggregation of CoOx in the pores of the carrier SBA-15 was effectively inhibited by the confinement effect, which further facilitated the formation of the main catalytic site Co(III) species. The results of the density-functional theory calculations further confirmed that Co(III) was the important catalytic site for CO oxidation. Compared with the catalyst prepared through the impregnation method, catalysts CoOx@SBA-15(X) exhibited a lower CO conversion temperature and activation energy for CO oxidation. In addition, the pore size of the carrier SBA-15 had a significant impact on the catalytic activity of CoOx, and the catalyst prepared with a larger pore size SBA-15 as carrier exhibited a higher catalytic activity. This result was mainly attributed to the fact that the confinement effect could effectively enhance the defect formation in metal oxides. Furthermore, the catalyst with a larger pore size SBA-15 as a carrier presented a higher content of Co(III) species, which significantly enhanced the catalytic activity of CoOx for CO oxidation. The results demonstrated that the pore structure of SBA-15 could affect the formation of the metal oxide (CoOx) species, which further significantly affected the catalytic activity of CoOx for CO oxidation. The results are expected to provide a strategy to synthesize efficient catalysts for CO oxidation by using ordered mesoporous materials. [Display omitted] •Solid state grinding method is an effective way to confine CoOx in SBA-15 pores.•Confinement effect could enhance the catalytic activity of catalysts for CO oxidation.•SBA-15 with larger pore size was more favorable for the formation of Co(III) species.